Methods of experimental evaluation of lateral forces (review) - A. M. Brzhezovskiy (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
On the basis of existing practice and analysis of domestic and foreign sources a classification of methods for experimental evaluation of the lateral forces of interaction between the wheel of the railway carriage and the rail head is given. A review of the various experimental methods implemented, using gauges, mounted on elements of track superstructure, is provided. Brief description of the principal methods of using the elastic properties of rails for the experimental evaluation of lateral forces using strain gauges is made. Article provides methods for measuring the lateral force, based on the registration of the forces acting from the rail to the sleeper, and special elastic rail sensing elements embedded in the rail neck. Current trends of improving registration system of lateral forces, including ways to "continuous" registration of the lateral forces are shown. Review includes recommendations for evaluating the adequacy of the measuring lateral forces on the basis of analysis of experimental data from a number of dynamic interaction processes in rolling stock and track interaction recorded simultaneously with the side forces on the same measurement track sections, including dynamic stresses in the edges of the rail foot of horizontal transverse forces, acting on the rail to the sleeper, frame strength.